2016
DOI: 10.1097/rlu.0000000000001039
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT Reveals Disease Remission in a Patient With Ipilimumab-Refractory Advanced Melanoma Treated With Pembrolizumab

Abstract: Pembrolizumab is an anti-programmed cell death receptor 1 (anti-PD-1) antibody, recently approved for the treatment of ipilimumab-refractory metastatic melanoma. We report on a 49-year-old patient with unresectable metastatic melanoma initially treated with 4 cycles of ipilimumab. Because of demonstration of progressive disease on PET/CT, the patient was enrolled into a clinical trial of pembrolizumab. After completion of 4 cycles of pembrolizumab, the follow-up PET/CT scans performed early after and 7 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In previous studies on the use of PET-based response in melanoma patients treated with ICIs, as many as half the patients showing residual disease on CT had negative findings on 18 F-FDG PET (23)(24)(25)(26). Indeed, the risk for PD misclassification after ICIs was higher in initial observations, which found that 10% of melanoma patients who, during ipilimumab, would have been misclassified as PD by World Health Organization criteria showed a clinical response (including PR and SD) (27). Subsequently, the rate of pseudoprogression was reported as 0%-6% in NSCLC treated with ICIs, and at present, pseudoprogression should be considered mainly when the clinical condition of a patient in apparent radiologic progression is concomitantly improving (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on the use of PET-based response in melanoma patients treated with ICIs, as many as half the patients showing residual disease on CT had negative findings on 18 F-FDG PET (23)(24)(25)(26). Indeed, the risk for PD misclassification after ICIs was higher in initial observations, which found that 10% of melanoma patients who, during ipilimumab, would have been misclassified as PD by World Health Organization criteria showed a clinical response (including PR and SD) (27). Subsequently, the rate of pseudoprogression was reported as 0%-6% in NSCLC treated with ICIs, and at present, pseudoprogression should be considered mainly when the clinical condition of a patient in apparent radiologic progression is concomitantly improving (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…IrRECIST and iRECIST seem to better identify patients with unconventional response as false progressors 94. Metabolic imaging like positron emission tomography (PET) tracers as 18 F-fluorodeoxyglucose (FDG) are known to be taken up in inflammatory cells, what may predict response to immunotherapy better than CT 9597…”
Section: Predictive Factors Of Response To Pembrolizumab and Selecmentioning
confidence: 99%
“…This suggests that FDG-PET may reflect therapeutic efficacy by the immune checkpoint inhibitors, considering the results of a recent study that indicated that FDG uptake after administration of nivolumab was an independent prognostic factor, and PD-L1 expression or plasma concentration of nivolumab was not a predictor of early therapeutic efficacy [ 42 ]. FDG-PET is supposed to be useful for monitoring early response to anti-PD-1 antibody, and several reports in the literature show the value of monitoring the anti-tumor efficacy of immune-checkpoint inhibitors; however, optimal timing to evaluate efficacy remains to be addressed [ 43 , 44 ]. Increased clinical use of immune checkpoint inhibitors determined the necessity of creating appropriate evaluation criteria using FDG-PET.…”
Section: Therapeutic Monitoring With Fdg-petmentioning
confidence: 99%